Correlation between severity of clinical signs and transcranial magnetic motor evoked potentials in dogs with intervertebral disc herniation. (March 2017) - Amendt, H.-L.; Siedenburg, J.S.; Steffensen, N.; Kordass, U.; Rohn, K.; Tipold, A.; Stein, V.M.
Highlights: Transcranial magnetic motor evoked potentials (TMMEPs) were taken in 50 dogs with thoracolumbar intervertebral disc herniation. An increase in onset latency and decrease in peak-to-peak amplitude were detected in TMMEPs of dogs with paraparesis. No TMMEPs could be generated in the pelvic limbs of paraplegic dogs. In paraplegic dogs with recovery of motor function, TMMEP reappeared. Reappearing TMMEPs were polyphasic, with increased onset latency and decreased peak-to-peak amplitudes. Abstract: Transcranial magnetic motor evoked potentials (TMMEPs) can assess the functional integrity of the spinal cord descending motor pathways. In intervertebral disc herniation (IVDH), these pathways are compromised to varying degrees reflected by the severity of neurological deficits. The hypotheses of this study were as follows: (1) TMMEPs differ in dogs with IVDH and healthy control dogs; (2) TMMEPs reflect different severities of neurological signs; and (3) TMMEPs can document functional motor improvement and therefore monitor recovery of function. TMMEPs were recorded in 50 dogs with thoracolumbar IVDH. Clinical signs ranged from spinal hyperesthesia to non-ambulatory paraparesis in 19 dogs and paraplegia with/without deep pain sensation in 31 dogs. In these 31 paraplegic dogs, transcranial magnetic stimulation (TMS) was repeated during follow-up examinations. Ten healthy Beagle dogs served as controls. There was a significant increase in onset latency and decrease in peak-to-peak amplitude in the pelvic limb TMMEPs of dogs with spinal hyperesthesia to severe paraparesis compared to control dogs. Waveforms in dogs with IVDH were predominantly polyphasic in contrast to the biphasic waveforms of the control dogs. TMMEPs could not be generated in the pelvic limbs of paraplegic dogs. However, TMMEPs with markedly increased onset latencies and decreased peak-to-peak amplitudes reappeared in the pelvic limbs of dogs that were paraplegic before surgery and showed functional motor improvement during follow-up. The severity of neurological deficits was reflected by TMMEP findings, which could be used to document functional motor recovery in IVDH. TMS could therefore be used as an ancillary test to monitor response to therapy in dogs during rehabilitation.